PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI BERORIENTASI LAB MINI DI SMA NEGERI NGORO JOMBANG - Fatikhatun Nikmatus Sholihah; Endang Susantini; Tukiran - (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2015)
This study aims to develop learning tools that will be oriented on mini laboratory at Senior Hight School Ngoro Jombang by using cooperative learning. This research uses R and D method (Research and Development) and trial design using one group pretest-posttest design with quantitative and qualitative descriptive analysis techniques. Based on the results of data analysis, it can be obtained some following results: 1) The feasibility of the learning tool is very good and feasible to use, 2) The effectiveness of learning tools can be seen from student learning result and students’ response, a) student learning result is 80,6% completed in cognitive competence and 100% in psychomotor, and it is very good in afective competences, b) the students have positive respons in their interests of learning process, 3) The practicality of learning tools can be seen from result of lesson plan done and obstacles that occured in learning process, a) the quality level of lesson plan done is high and obstacles that occured in teaching are the number of group members is too large. Based on the result of data analysis, it can be concluded that learning tools oriented on mini laboratory implemented uses cooperative learning is effective and practical on the topic of Fungi, but it is adjustable with the situaton and condition of the school specifically in the availbility of equipments in the laboratory. KEYWORD: learning tools, cooperative learning, mini laboratory